Development and characterization of a pseudovirus system for human Aichi virus: in vitro and in vivo analysis - Ruojun Wu; Jingli Tian; Shunchang Fan; Minyi Liang; Yucheng Li; Ying Deng; Binbin Tang; Minyi Zhang; Qing Chen (Virology Journal)
Abstract Human Aichi virus (AiV) (genus Kobuvirus, family Picornaviridae) has been described as a causative agent of human gastroenteritis since 1989. However, research on AiV at cellular and animal levels is limited. Utilizing a double reporter gene system, we constructed an AiV capsid protein plasmid and genomic backbone Replicon. Subsequently, AiV pseudovirus (AiV PsV) particles were packaged using a three-plasmid co-transfection system. Eleven cell types were screened to identify those susceptible to AiV PsV. Mouse models were established with AiV PsV to determine the optimal mouse species, mode of infection, and detection time, and investigate distribution characteristics of AiVs in vivo. HeLa cells exhibited the highest sensitivity to AiV PsV. A BALB/c mouse model established with bioluminescence imaging performed 24 h after infection via intraperitoneal injection demonstrated that the bioluminescent signal was concentrated in the murine abdominal cavity. The AiV PsV system should advance understanding of the infectious features of AiVs.